Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1108/jhom-06-2018-0176
|View full text |Cite
|
Sign up to set email alerts
|

Lean implementation in healthcare supply chain: a scoping review

Abstract: Purpose The purpose of this paper is to identify the lean production (LP) practices applied in healthcare supply chain and the existing barriers related to their implementation. Design/methodology/approach To achieve that, a scoping review was carried out in order to consolidate the main practices and barriers, and also to evidence research gaps and directions according to different theoretical lenses. Findings The findings show that there is a consensus on the potential of LP practices implementation in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 100 publications
(87 reference statements)
0
54
0
Order By: Relevance
“…In the pharmacy area, the VSM and unfolding tools stand out. This practice is usually cited as one of the first initiatives in the improvement implementation process, however as Borges et al (25) discusses, it is common the usage of value streams in the healthcare field as process flows or even a work operation (26) which may include materials, patients, medicines, equipment, services, among others.…”
Section: Lean Principles and Tools Usage In The Healthcare Fieldmentioning
confidence: 99%
“…In the pharmacy area, the VSM and unfolding tools stand out. This practice is usually cited as one of the first initiatives in the improvement implementation process, however as Borges et al (25) discusses, it is common the usage of value streams in the healthcare field as process flows or even a work operation (26) which may include materials, patients, medicines, equipment, services, among others.…”
Section: Lean Principles and Tools Usage In The Healthcare Fieldmentioning
confidence: 99%
“…This is considered important because of a widely felt need to improve the quality, accessibility and affordability of healthcare systems [5] and of hospitals in particular, given the fact that hospitals are a major cost item of the healthcare system [6]. There is a wide consensus in literature that an integrated perspective on hospitals, which is a central concept in supply chain management, and in lean and other operations management theories, can contribute to the improvement of hospital performance [4,[7][8][9][10][11][12]. Integrated hospitals plan patient processes and resources from the perspective of the total system [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ludwig et al found evidence that hospitals that perform well score high on cooperation, while efficient departments within a hospital don’t necessarily contribute to the hospital’s overall efficiency [ 8 ]. There are, however, a few studies that show system-wide performance improvement when adapting integrative practices such as lean [ 12 ]. In an earlier scoping study [ 13 ] we found that research on logistics in hospitals typically focuses on one specific logistical flow (patients, material or staff) or on specific departments, but not on a system-wide level.…”
Section: Introductionmentioning
confidence: 99%
“…found evidence that hospitals that perform well score high on cooperation, while efficient departments within a hospital don't necessarily contribute to the hospital's overall efficiency [8]. There are, however, a few studies that show system-wide performance improvement when adapting integrative practices such as lean [12]. In an earlier scoping study [13] we found that research on logistics in hospitals typically focuses on one specific logistical flow (patients, material or staff) or on specific departments, but not on a system-wide level.…”
Section: Introductionmentioning
confidence: 99%